Identifying hospital-acquired infections using retrospective record review from the Irish National Adverse Events Study (INAES) and European point prevalence survey case definitions. Issue 3 (March 2019) - Rafter, N.; Finn, R.; Burns, K.; Condell, S.; Conroy, R.M.; Hickey, A.; O'Connor, P.; Vaughan, D.; Walsh, G.; Williams, D.J.
Summary: Background: Point prevalence surveys (PPSs) collect data on hospital-acquired infections (HAIs) at one point in time but do not provide information on incidence over the entire admission or impact on patients or healthcare resources. Retrospective record review examines the entire admission to determine adverse event prevalence, incidence, preventability, physical impairment and additional length of stay. Aim: To establish whether European HAI surveillance definitions can be applied to the Irish National Adverse Events Study (INAES) retrospective record review data to determine HAI burden. Methods: In the INAES, 1574 admissions were reviewed using a two-stage methodology and 247 adverse events were found. These were examined against European HAI case definitions to determine whether the event was an HAI. Results were compared with the 2011/12 European PPS data for Ireland. Findings: The prevalence of HAI adverse events in INAES was 4.4% (95% confidence interval (CI) 3.1–6.1%) with an incidence of 3.8 (95% CI 2.5–5.2) HAI adverse events per 100 admissions. The PPS HAI prevalence for Ireland was 5.2%. HAI types and micro-organisms were similar in INAES and the PPS. Approximately three-quarters of INAES HAI adverse events were preventable, 7% caused permanent impairment and 7% contributed to death. A mean of 10 additional bed days were attributed to HAI adverse events, equivalent to €9400 per event. Conclusion: Retrospective record review is an accurate source of information on HAI incidence, preventability and impact that complements PPS prevalence rates. HAI adverse events result in higher costs to the healthcare system than other adverse events.